O ensino-aprendizagem de matemática através de projetos envolvendo profissões: um estudo de caso no ensino fundamental - Pêgo, Rudnei Nunes (2013)
This project is aimed to develop a possibility of teaching / learning to some mathematical issues and apply it through practical projects related to a profession, to increase student learning. In order to this it was done a case study with two classes of 8th grade (9th grade in the new nomenclature) of a public elementary school from Serra-ES involving the Architecture and Engineering professions, which were chosen with the classes. The contents worked were defined by the researcher, who was also the teacher of the discipline, based on their previous experience and items in which students typically encountered major difficulties, namely: Trigonometry of Rectangle Triangle and Areas of Plane Figures. The project was defined as: the construction of a school maquette and low plants of the school and the square, in scale. The students, organized in groups, were accompanied and assisted by the teacher throughout the entire project. The results were positive: the students were engaged and motivated; increased their selfesteem, decreased resistance towards Mathematics and the distance between theory and practice; encouraged the teamwork, improving the teacher-student and student-student relationships; and improved significantly students performance in evaluations compared to other classes or these same classes in other contents.